SISTEM INFORMASI PENJUALAN DI BOWLEH.SINI SIDOARJO MENGGUNAKAN METODE WATERFALL - Rizky Aditya Nugroho; Awang Andhyka; Achmad Alfi Rohman (Institut Teknologi Adhi Tama Surabaya, 2022)
Sales and marketing that use traditional methods or steps, namely by asking the closest people to inform other people about their products. In this technological era, this method is less profitable because it does not reach people who like to find product information on the internet. It takes an application in the form of a sales information system that can inform about products and can serve online orders so that it can attract more and more profitable customers. The purpose of doing this research is to build an application in the form of an informative and communicative sales information system for Bowlleh.sini Sidoarjo and the application is able to make it easier for consumers when they will place an order for products available on the Bowlleh.sini Sidoarjo website application online. This sales application information system was created using WordPress as its content management system and integrated with Midtrans as a means of payment when ordering products from Bowlleh.sini Sidoarjo. With the application in the form of a sales information system, it is expected to be able to provide information to prospective buyers and can be accessed at any time easily and quickly so as to increase the number of buyers and income.